Rent assistance and health: findings from Detroit - Kalousova, L; Evangelist, M (Taylor and Francis, 2018)
This study assesses the relationship between rent assistance and health in a longitudinal, population-representative sample collected in the Detroit metro area. Previous research has found that rent assistance recipients are less healthy than otherwise similar nonrecipients in the cross-section, but the evidence about the effects of rent assistance on health in the long run is ambiguous. Our study uses panel survey data to compare the health of recipients and eligible nonrecipients at the study’s onset and four years later at follow-up with respect to an extensive set of physical, mental and behavioural health outcomes. Our results demonstrate that rent assistance recipients are in worse overall health than non-recipients, but also provide suggestive evidence that the programme may buffer health declines in the medium term. However, the positive buffering effects may be erased in the long run, as we simultaneously observed an increase in smoking among rent assistance recipients. Our study shows that the current shortage of rent assistance may have implications for population health.